1957
DOI: 10.1001/archpedi.1957.02060040593001
|View full text |Cite
|
Sign up to set email alerts
|

I. Clinical Results and Effects on Proteinuria in One Hundred Six Instances

Abstract: Intially corticotropin (ACTH) and cortisone were used only to induce diuresis in children with the nephrotic syndrome, though occasional remissions were produced.1-7 Most of these early trials were of short duration and the amounts of drugs administered were small because of limited supplies and the occurrence of side-effects such as edema, hypertension, and hypokalemia. The demonstration that such changes could be prevented or minimized by means of diets rigidly restricted in sodium and high in potassium 8 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Five studies with 89 patients reported sustained proteinuria response with long-term treatment. The patients were predominantly pediatric (88 %; 341/388 with ages given) with age ≤20 years [ 10 , 13 , 14 , 17 , 31 – 40 ]. Report of proteinuria response was semi-quantitative, including marked reduction, absence or trace level, within normal limits and 1+ level.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies with 89 patients reported sustained proteinuria response with long-term treatment. The patients were predominantly pediatric (88 %; 341/388 with ages given) with age ≤20 years [ 10 , 13 , 14 , 17 , 31 – 40 ]. Report of proteinuria response was semi-quantitative, including marked reduction, absence or trace level, within normal limits and 1+ level.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term ACTH treatment results are summarized in Table 2 [ 13 , 17 , 38 40 ]. All regimens included an initial short-term daily ACTH treatment course.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations